An Organic FET SRAM With Back Gate to Increase Static Noise Margin and Its Application to Braille Sheet Display. - Takamiya, M. (IEEE Journal of solid state circuits)
An integrated system of organic FETs (OFETs) and plastic actuators is proposed, and it is applied to a Braille sheet display. Some circuit technologies are presented to enhance the speed and the lifetime for the Braille sheet display. An OFET SRAM is developed to hide the slow transition of the actuators. Developed five-transistor SRAM cell reduces the number of the bit lines by one-half and reduces the SRAM cell area by 20%. Pipelining the write-operation reduced the SRAM write-time by 69%. Threshold voltage control technology using a back gate increased the static noise margin of SRAM and compensated for the chemical degradation of the OFETs after 15 days. The oscillation frequency tuning range from -82% to +13% in a five-stage ring oscillator is also demonstrated with the threshold voltage control technology. The overdrive techniques for the driver OFETs reduced the transition time of the actuator from 34 s to 2 s. These developed circuit technologies achieved the practical 1.75-s operation to change all 144 Braille dots on Braille sheet display and will be essential for the future large area electronics made with OFETs